2010
DOI: 10.1111/j.1741-2358.2010.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of understanding levels of Indian dental students’ knowledge and perceptions regarding older adults

Abstract: Evaluation of understanding levels of Indian dental students' knowledge and perceptions regarding older adults Abstract Increasing numbers of older people and decreasing rates of edentulism highlight the importance of dental education that focuses on oral health and ageing. Our evaluation study was carried out to assess the Indian dental graduate's geriatric knowledge, as well as their awareness, of the bio-psychosocial factors that are potential barriers to geriatric oral health care. A total of 98 students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Rare studies have shown slightly hostile or indifferent standpoints of dentists to treat the elderly and a low level of knowledge about the ageing process and the needs of the elderly [17,18]. Similar results were conducted among dental students [19,20]. Dentists' views on the oral health of the elderly do not depend on the amount of knowledge on the subject, but on the frequency of encountering and treating these patients.…”
Section: Introductionmentioning
confidence: 53%
“…Rare studies have shown slightly hostile or indifferent standpoints of dentists to treat the elderly and a low level of knowledge about the ageing process and the needs of the elderly [17,18]. Similar results were conducted among dental students [19,20]. Dentists' views on the oral health of the elderly do not depend on the amount of knowledge on the subject, but on the frequency of encountering and treating these patients.…”
Section: Introductionmentioning
confidence: 53%
“…This point has been mentioned in other reports, as well. 27,33 The participants' score of self-reported oral health care practice for the elders was low. Following the educational intervention, the score improved markedly in the intervention group.…”
Section: Researchmentioning
confidence: 99%
“…Our finding on the improvement of the students' knowledge after educational intervention is in agreement with some other studies. 26,27 Teasdale and Shaikh conducted a CD-based educational tool to train students in geriatric oral health. They found that a self-instructional e-learning tool was effective in enhancing the students' knowledge.…”
Section: Researchmentioning
confidence: 99%
“…[2] Anehosur and Nadiger (2012) studied the attitude toward the elderly population in 98 5 th year students and concluded that there is a need to change the perspective of the students toward elderly by the inclusion of geriatric dentistry in the dental curriculum. [3] Komabayashi et al . studied the pattern of didactic, practical, and clinical activities taught in India as well as in Japan and found out that there is a considerable difference between two countries.…”
Section: Introductionmentioning
confidence: 99%
“…[4] India and Japan are two countries with fastest growing geriatric populations. [3] In absolute size of the aged population, the India ranks 4 th (population 77 million). [5] The average life expectancy at birth increased from 50.5 years for males and 49.0 years for females in 1970–1975 to 61.8 years for the males and 64.1 years for females in 1999–2001; it is expected to reach 69.8 years for males and 72.3 years for females by 2021–2025.…”
Section: Introductionmentioning
confidence: 99%